KEKERASAN SEKSUAL TERHADAP PEREMPUAN PERSPEKTIF FIKIH KLASIK - Suwarjin Suwarjin (Nuansa : Jurnal Studi Islam dan Kemasyarakatan, 2017)
Books circulating widely  in Indonesia and  viewed  as authoritative regarding sexual  issues  generally place women as subordinate men. Men are leaders and  rulers of women, while women as guided must  obey the husband’s command. The piety of a wife is measured by how far the devotion of her body soul to her husband. The virtuous wife is the one who never  demands his rights  from the husband, does  not go out and  give charity without the husband’s per- mission, does not raise his eyes and  voice in the presence of the husband, does not require knowledge except  with the permission of the husband, and  does  not worship the sunna without the blessing of the husband. If the husband does not grant his rights, then he must give up with sincerity to be saved from the terrible threat of God’s punishment. Related to intimate relationships, women are positioned as sex objects, not subjects. He should not delay the sexual desire of the husband, let alone reject  it. Such positions have an adverse effect on the wife. Wives often  experience sexual  violence and  neglected their  sexual rights.  The underlying perspective of husband-wife sexual relationships in the jurispruden- tial books  circulating in Indonesia is generally still classic  and  emphasizes only the  power  of men  against women in the  family. Such perspectives are no longer appropriate to the  present condition, in which  sexual  problems are seen as a common right that  should be practiced fairly between husband and  wife. Allegedly there has been a distortion of understanding of husband-wife sexual relationships that need to be straightened out, in order to avoid the impression, Islam legalize sexual violence in women